Protecting the Consumer Rights in the Digital Economic Era: Future Challenges in Indonesia - Arifin, Ridwan; Kambuno, Juan Anthonio; Waspiah, Waspiah; Latifiani, Dian (Jambura Law Review, 2021)
The emerging technological prospects affected many aspects, including consumer protection. The creation of data and computer-driven innovation would derive several advantages for consumers. Innovative products and services and new ways in which goods and services are developed and delivered. This paper aims to analyse how Indonesian legal policy on protection consumer rights in the digital era. The paper emphasized that it would advise against believing that policy is unreasonably permitted to give way to the technological agenda, whilst accepting that adaptations should be made and also that there should be a critical review of whether existing forms of regulation are needed in the digital economy of Indonesia. Regulations concerning to the protecting consumer rights in the world of e-commerce are still worrying even though many sectoral regulations have been promulgated, as well as weak supervision and lack of strict law enforcement in resolving consumer disputes. Trade regulation via the internet still raises many conceptual or theoretical questions that indicate the need to develop more detailed conceptual and theoretical explanations to the need for more complex laws and regulations to be able to protect consumers properly. More than that, national regulations are dealing with the context of trade through the internet, which transcends national boundaries without always being controlled through conventional means.